SISTEM INFORMASI PERSEDIAAN DONOR DARAH BERBASIS SUPPLY CHAIN MANAGEMENT DI PALANG MERAH INDONESIA (PMI) MEDAN - Rut Natalina Nababan; Humuntal Rumapea; Indra M. Sarkis (Universitas Methodist Indonesia, 2018)
Palang Merah Indonesia (PMI) is an independent and neutral organization in Indonesia whose activities are in the social field of humanity. PMI Medan City is overwhelmed by managing data on blood receipts from various places, this causes delays in information that should be informed to the public, the delay in disseminating information about blood stocks can have an impact on the difficulty of getting information on certain types of blood needs. The blood supply in PMI will later be distributed to the hospital. Many hospitals often have difficulty getting information or lack of public knowledge about how to obtain information about the availability of blood stock at PMI. Therefore we need an information system that can provide information quickly, well and accurately. To overcome this, a system will be developed that uses the concept of Supply Chain Management to control the blood supply in PMI. This system can control the blood donation process both during donation, the donation process, and finally for whom the blood is donated so that the blood stock information process can be maintained and will not lack.